Studies on cephalosporin-C production in an air lift reactor using different growth modes of Cephalosporium acremonium - Srivastava P.; Kundu S. (My University, 2025)
This paper deals with the studies on Cephalosporin-C production in a lab-scale airlift reactor using Cephalosporium acremonium. Various growth modes, viz. pellets and Siran supported bioparticles were used to improve the process over conventional free mycelial fermentation. Cephalosporin-C production was significantly improved by using bioparticles over the free mycelial culture, probably due to the enhanced mass transfer in the fermentation broth. However, the biofilm of the bioparticles became unstable as the fermentation proceeded, and increase in the free cells in the broth occurs. The maximum specific growth rate of free cells, pellets and Siran carrier were observed to be 0.037, 0.033 and 0.045 h-1, respectively. The oxygen transfer coefficient also improved for the immobilised modes (100 h- 1, 70 h-1 for Siran carrier and pellets) and thereby enhanced specific antibiotic productivity, 18-28% were observed.